Analisa Struktur Balok dengan Metode Momen (Studi Kasus: Proyek Pembangunan Grand Mall Batam) - Yayuk Setyaning Astutik (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2018)
The Grand Mall Batam Development Project with number of stories 30 and 1 basement. Footing Plan of this project using bore pile. Observations are made at the project construction site for data collection for 3 months in 2018. The beams used are dimensins of B350 x 750 dimensions with a top reinforcement of 6D20 mm, 2D12 mm for center reinforcement, 3D20 mm for bottom reinforcement and D10-200 mm for diameter distance. The calculation of the beam starts with the planning data on the beam structure analysis, namely Concrete Quality 29 Mpa (K-350), Screw 500 Mpa and Plain Iron 260 Mpa. The loading on the beam is carried out in the field that work, the child beam and the main beam with details of dead load, live load, factored load. On the main reinforcement of the beam, the moment is calculated, namely the moment of the field, the moment of support and the moment of the plan. Based on the calculation of loading on the beam, the deflection value is 0.01709 m. Calculation of stirrup reinforcement on the beam where the required distance is 254.0073 mm and a distance of 200 mm is taken with an iron diameter of 10 mm. So the calculation of the main reinforcement of beam and stirrup reinforcement is in the Safe category.